A Study of Training and Development at Private Educational Institutions- with special reference to Malwa Region- Punjab - Kaur, Rupinder; Prabhakar, Niti (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
This paper addresses the main issues of training and development for private sector particularly educational institutions. This Paper has been made to understand how training and development in private educational Institutions make a difference in the working style of employees. The involvement of the private sector to foster the improvement of the workforce can affect the entire economy. The operations of the companies in the formulation and implementation of the training is having its own potential to grow as a strategy. This provided opportunity to the professionals deserves an upgrading approach into their skills and to their careers. The paper is based on the author’s personal experience with more than 100 different training activities. The author has also had in-depth conversations with hundreds of employees and employers of private educational institutions.